Gerakan Literasi Keagamaan sebagai Strategi Pembinaan Karakter Religius pada Siswa Sekolah Dasar - Azizah, Isnaini Nur; Utami, Ratnasari Diah (QUALITY, 2023)
The Religious Literacy Movement as a Strategy for Developing Religious Character in Elementary School Students. The religious literacy movement is an activity that concentrates on sources of information related to religion. The existence of religious literacy is closely related to one's religious character, so that if religious literacy activities are driven, it will affect the increase in student religiosity. This study aims to describe the implementation of the religious literacy movement in elementary schools. The method used is qualitative in field research. Based on the results of research, the religious literacy movement is carried out on a daily, weekly or incidental basis. Daily prayers before and after studying, reading short letters, reading corners, dhuha and noon prayers. Then weekly activities, namely morning assembly filled with Islamic stories as well as reading verses of the Qur'an together and visiting the library. Incidental activities, namely the celebration of Islamic holidays, such as the splendor of Ramadan, Islamic boarding schools, Eid al-Fitr, Halal Bihalal and Isra Miraj commemoration. In the effort to implement the religious literacy movement, there are several supporting factors and inhibiting factors. Gerakan literasi keagamaan merupakan kegiatan yang berkonsentrasi pada sumber informasi yang berhubungan dengan agama. Keberadaan literasi keagamaan berkaitan erat dengan karakter religius seseorang, sehingga apabila kegiatan literasi keagamaan digerakkan, maka akan berpengaruh pada peningkatan religiusitas peserta didik. Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan gerakan literasi keagamaan di sekolah dasar. Metode yang digunakan adalah kualitatif dalam bentuk Field Research atau penelitian lapangan. Berdasarkan hasil penelitian gerakan literasi keagamaan dilaksanakan secara harian, mingguan maupun insidentil. Harian berupa berdoa sebelum dan sesudah belajar, membaca surat pendek, pojok baca, salat duha dan salat dzuhur. Kemudian kegiatan mingguan yaitu apel pagi yang diisi dengan cerita islami maupun membaca ayat Al-Qur’an secara bersama-sama dan kunjungan perpustakaan. Kegiatan insidentil yaitu perayaan hari besar islam, seperti semarak ramadhan, pesantren kilat, idul fitri, halal bihalal dan memperingati isra miraj. Dalam upaya pelaksanaan gerakan literasi keagamaan terdapat beberapa faktor pendukung maupun faktor penghambat.